Effect of echinacoside on kidney fibrosis by inhibition of TGF-β1/Smads signaling pathway in the db/db mice model of diabetic nephropathy - Tang FJ; Hao YR; Zhang X; Qin J (Dove Medical Press, 2017)
Fengjuan Tang,1 Yarong Hao,1 Xue Zhang,1 Jian Qin2 1Department of Geriatrics, 2Central Laboratory, Renmin Hospital of Wuhan University, Hubei, People’s Republic of China Abstract: Kidney fibrosis and renal tubular epithelial-to-mesenchymal transition (EMT) are the main pathological changes of diabetic nephropathy (DN), which eventually leads to end-stage renal disease. Previous studies have suggested that echinacoside (ECH) is antifibrotic in the liver. However, the effect of ECH on kidney fibrosis in DN and its mechanisms are unknown. This study was performed to explore the effect of ECH on kidney fibrosis and also the molecular mechanisms of ECH in a db/db mice model of DN. Our results showed that, relative to db/db mice, the mice in the ECH group had an improved general state and reduced blood glucose and 24-hour urinary protein levels. The deterioration of renal function was delayed due to treatment with ECH. We also observed that ECH can improve histopathological findings in the kidneys of db/db mice, including collagen deposition, mesangial cell and mesangial matrix hyperplasia, basement membrane thickening, and podocyte reduction. Moreover, ECH inhibited the TGF-β1/Smads signaling pathway, downregulated fibronectin (FN), collagen IV, and alpha-smooth muscle actin (α-SMA) levels, and upregulated E-cadherin level in the db/db mice model of DN. Our findings indicate that ECH has a therapeutic effect on DN, including the inhibition of renal tubular EMT and kidney fibrosis. Furthermore, ECH inhibits kidney fibrosis through regulation of the TGF-β1/Smads signaling pathway. Keywords: diabetic nephropathies, echinacoside, db/db mice, kidney fibrosis, EMT, TGF-β1/Smads signaling pathway